2012
DOI: 10.1021/jf204134w
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation of Indigenous Microbial Communities for Anaerobic Transformation of Pentachlorophenol in Paddy Soils of Southern China

Abstract: This study explored biostimulation mechanisms with an electron donor and a shuttle for accelerating pentachlorophenol (PCP) transformation in iron-rich soils. The results indicated that indigenous microbial communities are important for PCP transformation in soils. Biostimulation of indigenous microbial communities by the addition of lactate and anthraquinone-2,6-disulfonate (AQDS) led to the enhanced rates of PCP dechlorination by the dechlorinating-and ironreducing bacteria in soils. The electrochemical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Lactate, which acted as the electron donor, was important for microorganism metabolism and consequently accelerates microbial PCP degradation in paddy soils under anaerobic conditions. Our previous study also suggested that the microbial community structure can even be changed after biostimulation by the additions of lactate [65].…”
Section: The Pcp Mineralization Under Methanogenic (Anaerobic) Conditmentioning
confidence: 84%
“…Lactate, which acted as the electron donor, was important for microorganism metabolism and consequently accelerates microbial PCP degradation in paddy soils under anaerobic conditions. Our previous study also suggested that the microbial community structure can even be changed after biostimulation by the additions of lactate [65].…”
Section: The Pcp Mineralization Under Methanogenic (Anaerobic) Conditmentioning
confidence: 84%
“…The filtrate was collected for highperformance liquid chromatography (HPLC) analysis of the PCP concentration. Details of the HPLC analysis are provided elsewhere (Lan et al 2008;Chen et al 2012;Wang et al 2012;Tong et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, in the anaerobic environment, PCP degradation is a microbial dechlorinated respiration process, during which the chlorinated compounds serve as terminal electron acceptors (Saia et al 2007;Payne et al 2011). In our previous study, Chen et al (2012) revealed that the dechlorinated products of degradation of PCP are 2,3,5,6-tetrachlorophenol (TeCP) and 2,3,5-trichlorophenol (TCP), and Tong et al (2014) also found the similar intermediates in dechlorination of PCP. According to these reports, PCP is expected to be dechlorinated under anaerobic conditions by microbes at the ortho-position (Bouchard et al 1996;Field and Sierra-Alvarez 2008).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is relatively persistent, where it undergoes slow natural dissipation, by e.g. adsorption, volatilization, leaching and biodegradation (He et al, 2007;Chen et al, 2012;Puglisi et al, 2009). The main process leading to the dissipation of pesticide residues in soil is biological degradation, caused by the activities of soil microorganisms (RodriguezCruz et al, 2006;Vryzas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%